ECONOMIC SUBSTANTIATION OF REAL INVESTMENTS IN CONSTRUCTION OF OBJECTS OF SPHERE OF SERVICES IN A COUNTRYSIDE - J. V. Belozertseva (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
The analysis of opportunities of construction of the enterprises of sphere of services in a countryside in Southern Dagestan is lead. Features and requirements to designing the enterprises of sphere of services in a countryside are considered {examined}. The four-stage concentric model of rational territorial accommodation of the enterprises of sphere of services and the author's approach to an estimation of efficiency of investment civil-engineering designs of objects of sphere of services in a countryside are offered.